Comparative analysis of SmartArc‐based dual arc volumetric‐modulated arc radiotherapy (VMAT) versus intensity‐modulated radiotherapy (IMRT) for nasopharyngeal carcinoma - Lee, Tsair‐Fwu (J Appl Clin Med Phys, 2011)
The purpose of this study was to evaluate and quantify the planning performance of SmartArc‐based volumetric‐modulated arc radiotherapy (VMAT) versus fixed‐beam intensity‐modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC) using a sequential mode treatment plan. The plan quality and performance of dual arc‐VMAT (DA‐VMAT) using the [Formula: see text] Smart‐Arc system (clinical version 9.0; Philips, Fitchburg, WI, USA) were evaluated and compared with those of seven‐field (7F)‐IMRT in 18 consecutive NPC patients. Analysis parameters included the conformity index (CI) and homogeneity index (HI) for the planning target volume (PTV), maximum and mean dose, normal tissue complication probability (NTCP) for the specified organs at risk (OARs), and comprehensive quality index (CQI) for an overall evaluation in the 11 OARs. Treatment delivery time, monitor units per fraction (MU/fr), and gamma [Formula: see text] evaluations were also analyzed. DA‐VMAT achieved similar target coverage and slightly better homogeneity than conventional 7F‐IMRT with a similar CI and HI. NTCP values were only significantly lower in the left parotid gland (for xerostomia) for DA‐VMAT plans. The mean value of CQI at [Formula: see text] indicated a 2% benefit in sparing OARs by DA‐VMAT. The MU/fr used and average delivery times appeared to show improved efficiencies in DA‐VMAT. Each technique demonstrated high accuracy in dose delivery in terms of a high‐quality assurance (QA) passing rate [Formula: see text] of the [Formula: see text] criterion. The major difference between DA‐VMAT and 7F‐IMRT using a sequential mode for treating NPC cases appears to be improved efficiency, resulting in a faster delivery time and the use of fewer MU/fr. PACS number: 87.53.Tf, 87.55.x, 87.55.D, 87.55.dk